Kwaidan: Stories and Studies of Strange Things - Hearn, Lafcadio, 1850-1904 (Salt Lake City, UT : Project Gutenberg, 1998)
"Kwaidan: Stories and Studies of Strange Things" by Lafcadio Hearn is a collection published in 1904. This haunting volume gathers Japanese ghost stories translated from old texts, alongside tales told directly to Hearn and personal recollections. From vengeful spirits to supernatural encounters, these eerie narratives explore the mysterious world of Japanese folklore. The collection concludes with essays examining insects through the lens of Eastern beliefs, connecting butterflies, mosquitoes, and ants to concepts of souls, karma, and morality. (This is an automatically generated summary.)
The story of Mimi-Nashi-Hoichi -- Oshidori -- The story of O-Tei -- Ubazakura -- Diplomacy -- Of a mirror and a bell -- Jikininki -- Mujina -- Rokuro-Kubi -- A dead secret -- Yuki-Onna -- The story of Aoyagi -- Jiu-Roku-Zakura -- The dream of Akinosuke -- Riki-Baka -- Hi-Mawari -- Horai -- Butterflies -- Mosquitoes -- Ants.
Wikipedia page about this book: https://en.wikipedia.org/wiki/Kwaidan:_Stories_and_Studies_of_Strange_Things
Release date is 1998-02-01
an anonymous Project Gutenberg volunteer
Keywords: Ghost stories; Paranormal fiction; Japan -- Social life and customs -- Fiction; Legends -- Japan